2023
DOI: 10.1063/5.0159501
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-margin limiting mechanisms of AlScN-based HEMTs

Abstract: In this work, the off-state characteristics of AlScN/GaN high electron mobility transistors (HEMTs) grown by metalorganic chemical vapor deposition (MOCVD) were studied and directly compared to an AlGaN- and an AlN-HEMT grown in the same MOCVD. Pinch-off instability and leaky capacitive measurements were observed for AlScN-based HEMTs, which was correlated with a higher ideality factor and lower effective potential barrier height than the AlGaN and AlN-HEMTs. However, the reverse bias characteristics exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Schottkygate metallization is then evaporated, followed by gate-head passivation and formation of the source field plates. The gateto-source and gate-to-drain distances are 0.7 and 1.2 µm, respectively [9], [10]. Hall structures were realized to measure the sheet carrier density on passivated and isolated fields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schottkygate metallization is then evaporated, followed by gate-head passivation and formation of the source field plates. The gateto-source and gate-to-drain distances are 0.7 and 1.2 µm, respectively [9], [10]. Hall structures were realized to measure the sheet carrier density on passivated and isolated fields.…”
Section: Methodsmentioning
confidence: 99%
“…Transistors with a gate width of W G = 2 × 25 µm were used to determine the saturation current and transconductance of the fabricated devices experimentally. A detailed description of the fabrication, small/large signal, transfer, and OFF-state characteristics can be found in [9] and [10].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the lattice-matched growth of ScAlN to GaN [7] allows for higher barrier thickness compared to AlN, contributing to reduced gate-leakage current in Schottky-gate-diodes. This advantage, coupled with much higher carrier densities in the 2DEG than conventional AlGaN-HEMTs, positions ScAlN/GaN heterostructures as a highly attractive trade-off in terms of carrier density, barrier thickness, barrier strain, and voltage-margin [8,9]. Promising results have been demonstrated at the transistor level concerning output power (POUT) and power-added efficiency (PAE) [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth noting that only low-noise amplifiers (LNAs) have been reported on a circuit level in this early stage of development [11]. Several studies have reported on pinch-off issues and early soft/hard breakdown [8]. This technology holds promise for high-power applications, including RF switches [10,[12][13][14][15][16] power amplifiers [11], wireless communication [16,17] and radar systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…The recent focus of advanced contact processes is generally driven by CMOS-compatible, Au-free, and/or low-temperature budget ohmic contacts, [8][9][10][11][12] or n-GaN regrowth for highlyscaled AlGaN 5) or novel Al(Sc)N-based HEMTs [13][14][15] with high Al-content. The fabrication of highly n-type doped GaN films was demonstrated via Si implantation, 13,16,17) MBE, [18][19][20][21] MOCVD [22][23][24][25][26] (Si or Ge), pulsed laser deposition (PLD) 27) and reactive, pulsed sputtering (PVD) from a solid Ga target. 15,[28][29][30][31] Si implantation is used for GaN-devices but faces issues to achieve carrier densities and requires a high-temperature treatment to recover for the implantation damage.…”
mentioning
confidence: 99%